Advanced Concept for Radar Sounder (ACRAS - WP430 report) Processing for the Baseline Mission: Demonstration on Airborne Data - Scheiber, Rolf; Schneider, Rafael; Papathanassiou, Konstantinos; Prats, Pau (2008)
This document includes the analysis performed on airborne data for the algorithms developed in WP 410 of the ACRAS project. Analysis is perfromed for along track SAR focussing using VHF radar sounder data of the British Antarctic Survey (BAS) and cross-track clutter analysis at P-band using E-SAR data of DLR. Autofocus investigations are also performed using E-SAR data.